Estudo da imobilização de proteases para a síntese de oligolisinas - Fagundes, Fabio Pereira (2011)
Enzymatic synthesis of peptides using proteases has attracted a great deal of attention in recent years. One key challenge in peptide synthesis is to find supports for protease immobilization capable of working in aqueous medium at high performance, producing watersoluble oligopeptides. At present, few reports have been described using this strategy. Therefore, the aim of this thesis was to immobilize proteases applying different methods (Immobilization by covalent bound, entrapment onto polymeric gels of PVA and immobilization on glycidil metacrylate magnetic nanoparticles) in order to produce water-soluble oligopeptides derived from lysine. Three different proteases were used: trypsin, α-chymotrypsin and bromelain. According to immobilization strategies associated to the type of protease employed, trypsin-resin systems showed the best performance in terms of hydrolytic activity and oligopeptides synthesis. Hydrolytic activities of the free and immobilized enzymes were determined spectrophotometrically based on the absorbance change at 660 nm at 25 °C (Casein method). Calculations of oligolysine yield and average degree of polymerization (DPavg) were monitored by 1H-NMR analysis. Trypsin was covalently immobilized onto four different resins (Amberzyme, Eupergit C, Eupergit CM and Grace 192). Maximum yield of bound protein was 92 mg/g, 82 mg/g and 60 mg/g support for each resin respectively. The effectiveness of these systems (Trypsin-resins) was evaluated by hydrolysis of casein and synthesis of water-soluble oligolysine. Most systems were capable of catalyzing oligopeptide synthesis in aqueous medium, albeit at different efficiencies, namely: 40, 37 and 35% for Amberzyme, Eupergit C and Eupergit CM, respectively, in comparison with free enzyme. These systems produced oligomers in only 1 hour with DPavg higher than free enzyme. Among these systems, the Eupergit C-Trypsin system showed greater efficiency than others in terms of hydrolytic activity and thermal stability. However, this did not occur for oligolysine synthesis. Trypsin-Amberzyme proved to be more successful in oligopeptide synthesis, and exhibited excellent reusability, since it retained 90% of its initial hydrolytic and synthetic activity after 7 reuses. Trypsin hydrophobic interactions with Amberzyme support are responsible for protecting against strong enzyme conformational changes in the medium. In addition, the high concentration of oxirane groups on the surface promoted multi-covalent linking and, consequently, prevented the immobilized enzyme from leaching. The aforementioned results suggest that immobilized Trypsin on the supports evaluated can be efficiently used for oligopeptides synthesis in aqueous media